Influence of Socio-Cultural factors on Rural House Form in Taraba State of Nigeria. - Ochapa, Adadu; Folorunsho, Eyiaromi Ademileke (NIU Journal of Social Sciences; Vol 3 No 2 (2017): KIU Journal of Social Sciences, Vol. 3 No. 2, September 2017, 2017)
This study investigates the Influence of Socio-Cultural factors on Housing Form in Rural Environment Among various ethnic groups of Taraba State, Nigeria with the aim to understand the socio-cultural factors that influences housing form adopted by tribes. A population of 2,300,736 (NPC, 2006) and a sample size of 750 house-hold head were selected for this study comprised of 135(18%) Mumuye, 86(11.47%) Jukun, 120(16%) Tiv, 95(12.67%) Mambila, 175(23.33%) Fulani, 105(14%) Wurukum and 34(4.53%) belong to other minority tribes. A Multistage Sampling technique was employed in the process of data collection. The study is a descriptive survey design with the main instruments used in collecting the data was “Questionnaire and in-depth interview (IDI) with a reliability index of 0.818 and validity of 0.90. Results are presented using simple percentage and the hypothesis was analyzed using chi-square statistics. The findings revealed that Traditional Single Hut Form (TSHF) is synonymous to Mumuye ethnic group belongs to low income class, while Traditional Compound Form (TCF) is synonymous to Jukun and Fulanis ethnic group belongs to low and middle income classes. The Fulani ethnic group were the majority in the use Jointed Block of Traditional Form (JBTF) and Jointed Block of Modern Building Form (JBMBF) of middle income classes. This study area socio-economic activity is agrarian in nature; Mumuye ethnic groups were the majority in food crop farming followed by Tiv and Mambila ethnic group. Tiv ethnic group are the majority in cash crop farmland followed by Jukun ethnic group, The Fulani ethnic dominated the animal husbandry (pastoral Farmland), while Fish farming was dominated by Wurukum ethnic group. The hypothesis revealed that Housing forms are not the same among the various ethnic groups in the study area. The researchers therefore recommend that when Wurukum tribe in any part of the country need to be resettled by government it should be near fishing water source, Fulanis near grassing field, Mumuye, Tivs and Mambila ethnic groups near farmable land. Key words: Socio-cultural, Housing forms, culture, Beliefs, influence.